Changes in Transforming Growth Factor-β1 in Gingival Crevicular Fluid of Patients with Chronic Periodontitis Following Periodontal Flap Surgery - Vikram, Vignesh (J Clin Diagn Res, 2015)
Introduction: The aim of the study was to assess changes in Transforming Growth Factor– β1 (TGF-β1) levels in gingival crevicular fluid (GCF) and examine correlation of TGF-β1 levels and periodontal parameters: probing pocket depth (PPD) and clinical attachment level (CAL) in sites with chronic periodontitis at various time intervals before and after periodontal surgery. Materials and Methods: The effects of non-surgical and surgical therapy on periodontal parameters and GCF TGF-β1 levels in 18 sites affected with chronic periodontitis were assessed upto 6 weeks post conventional flap surgery. GCF was collected and PPD, CAL recorded at Baseline. GCF was collected and PPD, CAL recorded at Pre-surgery and flap surgery performed. GCF was collected from all sites at Two Weeks Post-surgery. GCF was collected and PPD, CAL recorded at Six Weeks Post-surgery. The concentration of TGF-β1 in GCF was determined using a human TGF-β1 enzyme immunometric assay kit. Results: Mean TGF-β1 concentrations were significantly reduced at Pre-surgery, at Two Weeks Post-surgery and at Six Weeks Post-surgery (p<0.05) when compared to Baseline TGF-β1 values. There was a statistically significant reduction in PPD and gain in CAL following non-surgical and surgical therapy when compared to baseline (p<0.05). Conclusion: Results indicate that TGF-β1 may play a role in the pathogenesis and diagnosis of periodontal disease and could be considered as a disease predictive biomarker.